Multimedia Gloss Presentation: Learners' Preference and the Effects on EFL Vocabulary Learning and Reading Comprehension - Wang, Shufang; Lee, Chang In (Frontiers in Psychology, 2021)
Drawing on Moreno’s cognitive-affective theory of learning with media, this research aims to investigate the effectiveness of different multimedia glosses on learners’ vocabulary acquisition and reading comprehension in a CALL environment. A total of 160 university students who learnt English as a foreign language (EFL) in four classes participated in the study and were exposed to one of the four conditions: (a) L2 definition only, (b) L2 definition coupled with audio, (c) L2 definition plus video and (d) L2 definition with picture. Participants were asked to read eight hypermediated reading texts. Reading comprehension as well as vocabulary acquisition were measured using a pretest-posttest design. The results show first that all these four conditions led to students’ vocabulary gains. More specifically, participants who had access to L2 definition plus picture and plus videos achieved significantly higher scores than the other two groups, L2 definition coupled with audio and L2 definition only. Concerning reading comprehension, all multimedia glossing presentation led to better reading comprehension but no differences were found among all the glossing groups. The questionnaire and interviews data indicate that students preferred L2 definition coupled with video and picture glosses, followed by audio and L2 definition only. The results reflect that multimedia glossing presentation creates a different effect on students’ vocabulary acquisition and reading comprehension, respectively. They also provide pedagogical implications for learning in times of COVID-19.